At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] intercepts for the equation [tex]\(y = -6x + 3\)[/tex], follow these steps:
### 1. Finding the [tex]\(x\)[/tex]-intercept:
The [tex]\(x\)[/tex]-intercept occurs where [tex]\(y = 0\)[/tex].
1. Set [tex]\(y\)[/tex] to 0 in the equation [tex]\(y = -6x + 3\)[/tex]:
[tex]\[ 0 = -6x + 3 \][/tex]
2. Solve for [tex]\(x\)[/tex]:
[tex]\[ 6x = 3 \][/tex]
[tex]\[ x = \frac{3}{6} = \frac{1}{2} \][/tex]
3. Therefore, the [tex]\(x\)[/tex]-intercept is [tex]\(\left(\frac{1}{2}, 0\right)\)[/tex].
### 2. Finding the [tex]\(y\)[/tex]-intercept:
The [tex]\(y\)[/tex]-intercept occurs where [tex]\(x = 0\)[/tex].
1. Set [tex]\(x\)[/tex] to 0 in the equation [tex]\(y = -6x + 3\)[/tex]:
[tex]\[ y = -6(0) + 3 \][/tex]
2. Solve for [tex]\(y\)[/tex]:
[tex]\[ y = 3 \][/tex]
3. Therefore, the [tex]\(y\)[/tex]-intercept is [tex]\((0, 3)\)[/tex].
### Final Answer:
The intercepts for the equation [tex]\(y = -6x + 3\)[/tex] are:
- [tex]\(x\)[/tex]-intercept: [tex]\(\left(\frac{1}{2}, 0\right)\)[/tex]
- [tex]\(y\)[/tex]-intercept: [tex]\((0, 3)\)[/tex]
So the correct option is:
- [tex]\(\left(\frac{1}{2}, 0\right)\)[/tex] and [tex]\((0, 3)\)[/tex]
### 1. Finding the [tex]\(x\)[/tex]-intercept:
The [tex]\(x\)[/tex]-intercept occurs where [tex]\(y = 0\)[/tex].
1. Set [tex]\(y\)[/tex] to 0 in the equation [tex]\(y = -6x + 3\)[/tex]:
[tex]\[ 0 = -6x + 3 \][/tex]
2. Solve for [tex]\(x\)[/tex]:
[tex]\[ 6x = 3 \][/tex]
[tex]\[ x = \frac{3}{6} = \frac{1}{2} \][/tex]
3. Therefore, the [tex]\(x\)[/tex]-intercept is [tex]\(\left(\frac{1}{2}, 0\right)\)[/tex].
### 2. Finding the [tex]\(y\)[/tex]-intercept:
The [tex]\(y\)[/tex]-intercept occurs where [tex]\(x = 0\)[/tex].
1. Set [tex]\(x\)[/tex] to 0 in the equation [tex]\(y = -6x + 3\)[/tex]:
[tex]\[ y = -6(0) + 3 \][/tex]
2. Solve for [tex]\(y\)[/tex]:
[tex]\[ y = 3 \][/tex]
3. Therefore, the [tex]\(y\)[/tex]-intercept is [tex]\((0, 3)\)[/tex].
### Final Answer:
The intercepts for the equation [tex]\(y = -6x + 3\)[/tex] are:
- [tex]\(x\)[/tex]-intercept: [tex]\(\left(\frac{1}{2}, 0\right)\)[/tex]
- [tex]\(y\)[/tex]-intercept: [tex]\((0, 3)\)[/tex]
So the correct option is:
- [tex]\(\left(\frac{1}{2}, 0\right)\)[/tex] and [tex]\((0, 3)\)[/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.